2004
DOI: 10.1021/np049903m
|View full text |Cite
|
Sign up to set email alerts
|

New Cytotoxic Cembranes from the Sea Pen Gyrophyllum sibogae

Abstract: Two new cembrane-type diterpenoids have been isolated from the 2-propanol extract of the sea pen Gyrophyllum sibogae collected in South Africa: 7,8-dihydroflabellatene A (1) and 7,8-dihydroflabellatene B (2). Their structures were determined on the basis of detailed spectroscopic analysis and by single-crystal X-ray analysis of the major metabolite 1, which showed strong in vitro cytotoxicity against a panel of 13 tumor cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Previous studies have shown that the psammaplins, also bromotyrosine derivatives, inhibit HDACs. 16 HDAC inhibitors are a promising new class of anticancer agents that act by inhibiting cell proliferation and inducing cell cycle arrest in several cancer cell types. To analyze whether the antiproliferative effect of aplyzanzine B ( 1 ) and anomoian B ( 2 ) was related to the HDAC inhibition, A549 cells were treated with both compounds at different concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that the psammaplins, also bromotyrosine derivatives, inhibit HDACs. 16 HDAC inhibitors are a promising new class of anticancer agents that act by inhibiting cell proliferation and inducing cell cycle arrest in several cancer cell types. To analyze whether the antiproliferative effect of aplyzanzine B ( 1 ) and anomoian B ( 2 ) was related to the HDAC inhibition, A549 cells were treated with both compounds at different concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Diterpenes are a large class of structurally diverse natural products which are widely found in marine organisms, including Dictyota species [ 7 ]. Some diterpenes are promising drug candidates due to their remarkable pharmacological activity [ 8 , 9 , 10 ]. Some diterpenes from Dictyota species are considered as the characteristic constituents of this genus, and give them taxonomic significance [ 1 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…482-487, 519 [147,148] Leptogorgia alba 473, 474 [138] Leptogorgia laxa 155, 156 [59] Leptogorgia setacea 475, 476 [142] Lophogorgia peruana 157, 462-471, 526 [60,[137][138][139][140]143] Pseudopterogorgia sp. 532 [159] Pseudopterogorgia bipinnata 531, 619 [158] Pseudopterogorgia kallos 527-530 [134] Gorgonacea Plexaura flexuvsa 557 [163] Sea pen Gyrophyllum sibogae 66, 67 [31] Pseudopterogorgia acerosa 477 [143] Tetralophuzia setifomis 106 […”
Section: Resultsmentioning
confidence: 99%
“…Compound 66 showed the activity against all of the lines tested. GI 50 values (μM) for some of the lines evaluated are: DU-145 (82.0), IGROV (90.3), K-562 (62.7), and HT-29 (14.5) [31].…”
Section: Isopropyl Cembranesmentioning
confidence: 99%